Evaluating the antifibrotic potential of naringenin, asiatic acid, and icariin using murine and human precision‐cut liver slices - Ke Luo; Yana Geng; Dorenda Oosterhuis; Vincent E. deMeijer; Peter Olinga (Physiological Reports)
Abstract Liver fibrosis is an exaggerated wound healing response defined by the excessive accumulation of extracellular matrix. This study investigated the antifibrotic potential of naringenin (NRG), asiatic acid (AA), and icariin (ICA) using murine and human precision‐cut liver slices (PCLS). These natural products have shown promise in animal models, but human data are lacking. In this study, PCLS prepared from male mouse liver tissue (mPCLS), healthy human liver tissue (hhPCLS), and cirrhotic human liver tissue (chPCLS) were cultured for 48 h with varying concentrations of the three compounds. Our findings indicate that NRG reduced collagen type 1 (COL1A1) expression in a concentration‐dependent manner in both mPCLS and chPCLS, decreased fibrosis‐related gene expression, and significantly lowered pro‐collagen type 1 (PCOL1A1) levels in the culture medium by 54 ± 21% (mPCLS) and 78 ± 35% (chPCLS). Furthermore, NRG effectively inhibited IL‐1β and TNF‐α in mPCLS and IL‐1β in chPCLS on both gene and protein levels. AA specifically reduced COL1A1 and PCOL1A1 in chPCLS, while ICA selectively downregulated Col1a1 and Acta2 gene expression in mPCLS. This study suggests NRG's potential as an effective antifibrotic agent, warranting further investigation into its mechanisms and therapeutic applications in liver fibrosis.